Pengaruh Motivasi Berwirausaha dan Efikasi Diri Terhadap Minat Mahasiswwa Berwirausaha - Saryadi, Saryadi; Liss Dyah Dewi Arini; Bangun Prajadi Cipto Utomo (HATTA : Jurnal Pendidikan Ekonomi dan Ilmu Ekonomi, 2024)
Background: Motivation is very important for entrepreneurs. Besides motivation, self-efficacy will also affect entrepreneurial interest. Confidence supported by confidence based on self-assessment is very important for prospective entrepreneurs. Purpose. This study aims to determine the influence of entrepreneurial motivation variables and self-efficacy individually/partially or jointly or simultaneously on entrepreneurial interest. Method: This research is a type of quantitative research to provide empirical evidence of the influence of motivation on entrepreneurial interest, self-efficacy on entrepreneurial interest and together the influence of motivation and self-efficacy on entrepreneurial interest. The population was taken by purposive sampling by taking a sample of 103 respondents, consisting of 9 students from the Faculty of Health Sciences of the ARS study program and 50 students from class 21a1 of the RMIK study program. Faculty of Law and Business with a total of 44 students in class 22A1. Data analysis with multiple linear regression and statistical tests and classical assumptions Findings: The conclusions obtained show that there is a partial influence of entrepreneurial motivation has a significant positive effect on entrepreneurial interest, self-efficacy has a significant positive effect on entrepreneurial interest, motivation and self-efficacy simultaneously or together have a significant positive effect on entrepreneurial interest. The determination coefficient of 0.852 means that the variability of the influence of entrepreneurial motivation and self-efficacy on entrepreneurial interest is 85.2% while the remaining 14.8% is influenced by other variables that are not a research model. Conclusions: Self-efficacy has a greater effect than entrepreneurial motivation.